Combined effect of end-rounded versus tapered bristles and a dentifrice on plaque removal and gingival abrasion - CAPOROSSI,Leonardo Stephan (2016)
Abstract Two previous clinical studies evaluated the effect of end-rounded versus tapered bristles of soft manual brushes on the removal of plaque and gingival abrasion. However, the combined effect of an abrasive dentifrice on these outcomes has yet to be understood. The purpose of the present study was to compare the incidence of gingival abrasion and the degree of plaque removal obtained after the use of toothbrushes with tapered or end-rounded bristles in the presence or absence of an abrasive dentifrice. The study involved a randomized, single-blind, crossover model (n = 39) with a split-mouth design. Subjects were instructed to refrain from performing oral hygiene procedures for 72 hours. Quadrants were randomized and subjects brushed with both types of toothbrushes using a dentifrice (relative dentin abrasion = ± 160). Plaque and gingival abrasion were assessed before and after brushing. After 7 days, the experiment was repeated without the dentifrice. The average reduction in plaque scores and the average increase in the number of abrasion sites were assessed by repeated-measures ANOVA and Bonferroni’s post-hoc tests. End-rounded bristles removed significantly more plaque than tapered bristles, regardless of the use of a dentifrice. The dentifrice did not improve plaque removal. In the marginal area (cervical free gingiva), no difference in the incidence of gingival abrasion was detected between toothbrush types when used with a dentifrice (p ≥ 0.05). However, the dentifrice increased the incidence of abrasion (p < 0.001), irrespective of the toothbrush type tested. End-rounded bristles therefore removed plaque more effectively without causing a higher incidence of gingival abrasion when compared with tapered bristles. An abrasive dentifrice can increase the incidence of abrasion, and should be used with caution by individuals who are at risk of developing gingival recession.